Faktor-Faktor yang Mempengaruhi Undeprricing Saham pada Perusahaan Non Keuangan yang Melakukan Initial Public Offering (IPO) - Kamila, Tasya; Fitriasuri, Fitriasuri (Universitas Muhammadiyah Metro, 2023)
The underpricing phenomenon is a condition when stock price in primary market (IPO) is lower than that stock price in secondary market. This study aims to analyze the effect of profitability, liquidity, financial leverage, firm size, share offering percentage, underwriter reputation and auditor reputation to the level of underpricing of share in non financial companies that conduct initial public offering on Indonesia Stock Exchange for the 2019-2021 period. The samples were 109 non financial companies which has been selected by using the pusposive sampling technique. This study uses quantitative analysis techniques with multiple linear regression with the help of SPSS. The study results showed that firm size, share offering percentage and underwriter reputation had significant influence to the level of underpricing where as profitability, liquidity, financial leverage and auditor reputation had did not significantly influence on the level of underpricing.